Trend of albumin nanoparticles in oncology: a bibliometric analysis of research progress and prospects - Liu, Ye; Li, Yi; Shen, Wei; Li, Min; Wang, Wen; Jin, Xin (Frontiers in Pharmacology, 2024)
Background Delivery systems based on albumin nanoparticles (NPs) have recently garnered substantial interest in anti-tumor drug development. However, systematic bibliometric analyses in this field remain lacking. This study aimed to analyze the current research status, hotspots, and frontiers in the application of albumin NPs in the field of oncology from a bibliometric perspective. Methods Using the Web of Science Core Collection (WOSCC) as the data source, retrieved articles were analyzed using software, such as VOSviewer 1.6.18 and CiteSpace 6.1.6, and the relevant visualization maps were plotted. Results From 1 January 2000, to 15 April 2024, 2,262 institutions from 67 countries/regions published 1,624 articles related to the application of albumin NPs in the field of oncology. The USA was a leader in this field and held a formidable academic reputation. The most productive institution was the Chinese Academy of Sciences. The most productive author was Youn YS, whereas Kratz F was the most frequently co-cited author. The most productive journal was the International Journal of Nanomedicine, whereas the Journal of Controlled Release was the most co-cited journal. Future research hotspots and frontiers included “rapid and convenient synthesis methods predominated by self-assembly,” “surface modification,” “construction of multifunctional NPs for theranostics,” “research on natural active ingredients mainly based on phenolic compounds,” “combination therapy,” and “clinical applications.” Conclusion Based on our bibliometric analysis and summary, we obtained an overview of the research on albumin NPs in the field of oncology, identified the most influential countries, institutions, authors, journals, and citations, and discussed the current research hotspots and frontiers in this field. Our study may serve as an important reference for future research in this field.